Split Application of Potassium Reduces Rice Chalkiness by Regulating Starch Accumulation Process Under High Temperatures - Xinyue Zhang; Youfa Li; Junjie Dong; Yuanze Sun; Haowei Fu (Agronomy)
Chalkiness in rice is adversely affected by high temperatures during the flowering and grain-filling stages. Potassium (K) is essential for improving grain quality and heat resilience. The effects of split application K fertilizer on rice chalkiness under high temperatures during the flowering and grain-filling stages were investigated in this study. Four treatments, including ambient temperatures with basal K fertilizer (AT-K1), high temperatures with basal K fertilizer (HT-K1), high temperatures with 70% K pre-transplanting and 30% K at the heading stage (HT-K2), and high temperatures with 30% K pre-transplanting and 70% K at the heading stage (HT-K3), were conducted. The results revealed that the chalky grain rate and chalkiness degree were reduced by 9.2–13.72% and 12.16–19.91%, respectively, by the split application of K fertilizer through effectively modulating the sucrose-to-starch conversion process in the rice grains, relative to the single basal application of K fertilizer under high temperatures. Specifically, the split application of K fertilizer reduced the enzymatic activities of SuSy, ADPGase, and SBE by 3.17–34.20% at 5–10 DAA, and GBSS and SSS by 6.48–13.50% at 5 DAA, but enhanced them by 5.50–54.90% from 15 DAA and 2.07–97.10% from 10 DAA. Similarly, the gene expression levels of enzymes involved in this process were decreased by 3.52–24.12% at 5 DAA but increased by 8.61–30.00% at 20 DAA by the split application of K fertilizer. This modulation led to a retardation in the excessive accumulation of starch during the early grain-filling stage but a higher starch accumulation rate during the middle and later stages, combined with a longer duration of starch accumulation, ultimately resulting in higher starch accumulation and reduced rice chalkiness. These results suggest that the application of K fertilizer during the heading stage is effective in compensating the deterioration of rice chalkiness by high temperatures.